2017
DOI: 10.1039/c6ra25313j
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ultra-high molecular weight poly(methyl methacrylate-co-butyl acrylate-co-acrylic acid) under ultra violet irradiation

Abstract: A new acrylic terpolymer, poly(methyl methacrylate-co-butyl acrylate-co-acrylic acid) [P(MMA-co-BA-co-AA)] of ultra-high molecular weight (UHMW) was synthesized via seeded emulsion polymerization. This polyacrylic showed good film properties; high transparency, water resistance and mechanical flexibility that may suitable for many environmental based applications such as coating, packaging, label sensors etc. In order to access the photo-stability of this material for environmental application, studies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 21 publications
(12 reference statements)
2
36
0
1
Order By: Relevance
“…Furthermore, minor changes in band intensities were observed, evidencing chemical changes in the copolymer upon UV irradiation. The band underwent prominent changes is the carbonyl (C=O) stretching, which variation, as previously reported [52], was quantified after UV exposure. Indeed, considering the decrease of this band, the relative amount of the remaining functional group was determined by the ratio of IR absorbance at 1726 cm −1 after aging and the absorbance of the unexposed sample (Figure 4a) [55].…”
Section: Accelerated Agingmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, minor changes in band intensities were observed, evidencing chemical changes in the copolymer upon UV irradiation. The band underwent prominent changes is the carbonyl (C=O) stretching, which variation, as previously reported [52], was quantified after UV exposure. Indeed, considering the decrease of this band, the relative amount of the remaining functional group was determined by the ratio of IR absorbance at 1726 cm −1 after aging and the absorbance of the unexposed sample (Figure 4a) [55].…”
Section: Accelerated Agingmentioning
confidence: 81%
“…Figure 3a shows the FTIR spectra of nonirradiated copolymer without and with 10 wbm% of silica. The spectrum of the neat polymer (Figure 3a [52]. After the addition of the inorganic components (Figure 3a, black curve), strong absorption bands appear at 1118 and 476 cm −1 due to Si-O-Si stretching and bending, respectively, and at 1068 cm −1 related to Si-O bending.…”
Section: Accelerated Agingmentioning
confidence: 99%
“…Most studies were conducted to gain insight about the lifetime of homopolymer's upon exposure to sunlight or their usefulness as photoresist . Two major processes caused by UV irradiation were identified: photoinduced degradation and crosslinking, with the amount crosslinking being quantified simply by determining the mass of the insoluble fraction forming from a former soluble homopolymer . It was found that polyacrylates tend to crosslink more than the respective polymethacrylates and that longer aliphatic ester side chains resulted in more photo‐crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…Acrylated resins are used predominantly in oligomer systems and their combinations include epoxy, polyester and urethane prepolymers. They all contain a carbonyl group (Thompson, 2004;Du, et al, 2017;Shanti, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%